The multiple self and psychological openness - Suszek, Hubert; Kopera, Maciej; Jakubczyk, Andrzej (Frontiers in Psychology, 2025)
IntroductionThis research identifies and explores two distinct modes of self-experience and their influence on psychological openness. We distinguish between the unitary self-mode, where individuals perceive themselves as cohesive, stable entities, and the multiple self-mode, where they recognize their diverse, context-dependent aspects. These modes represent fundamentally different ways of experiencing and organizing self-knowledge that can be situationally activated. While both modes of self-experience have been theoretically described, their influence on psychological functioning remains empirically unexplored.MethodsThrough five experiments (N = 989), we tested whether activation of the multiple self-mode increases psychological openness compared to activation of the unitary self-mode using different experimental manipulations and measures.ResultsInduction of the multiple self enhanced psychological openness compared to induction of the unitary self. This effect was consistently observed across various domains of openness: openness as a state (Study 1, N = 204), openness to change (Studies 3 and 4, N = 230 and N = 184), range of values (Studies 2 and 3, N = 212 and N = 230), psychological mindedness and decentering (Study 5, N = 159). Results consistently showed moderate effect sizes (d = 0.31–0.44) across different operationalizations of both the multiple self-induction and openness measures.DiscussionThese findings indicate that the way in which individuals organize their self-knowledge has important implications for their cognitive and experiential flexibility, contributing to our understanding of personality plasticity and development.